CAN INCREASED MONOCYTE / LYMPHOCYTE RATIO BE USED AS AN INDICATOR FOR ALZHEIMER’S DISEASE? - Bolayır, Aslı (International Journal of Research -GRANTHAALAYAH, 2018)
Background: The monocyte to lymphocyte ratio (MLR) obtained by dividing the number of monocytes by lymphocyte number is considered as a new marker of inflammation. The role of MLR in Alzheimer’s disease (AD) has not been clearly understood yet. So, the aim of this study is to determine the role of MLR in the pathogenesis of AD. Method: Our study is a single centered retrospective study. 254 patients with AD, who applied to our clinic between January 2013 and December 2017 and 256 healthy control with similar age and sex were included to this study. Results: While lymphocyte count was lower in the control group; MLR values were higher in the patient group. The patient group was then divided into three subgroups according to the results of standardized mini mental test (SMMT). MLR values increased in parallel with the severity of AD. In addition, ROC analysis revealed that MLR values above 0.28 can be used as a marker of the development of AD (AUC: 0.76, 95% CI: 0.66–0.87, sensitivity: 73.1%, specificity of 81.1%). Conclusions: This study demonstrated the role of MLR in the inflammatory process, thought to be responsible for the development of AD.